2022
DOI: 10.3389/fgene.2022.999132
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of pharmacogenetic candidate genes affect etomidate anesthesia susceptibility

Abstract: Purpose: Etomidate is widely used in general anesthesia and sedation, and significant individual differences are observed during anesthesia induction. This study aimed to explore the molecular mechanisms of different etomidate susceptibility at the genetic level.Methods: 128 patients were enrolled in the study. The bispectral index (BIS), mean arterial pressure (MAP) and heart rate (HR) were recorded when the patients entered the operating room for 5 min, before the administration of etomidate, 30 s, 60 s, 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The genetic contribution to the effi cacy and safety profi le of etomidate is still poorly understood. One study showed that GABRA2 rs279858, GABRB2 rs2561, CYP2C9 rs1559 and UGT1A9 rs11692021 variants were associated with individual diff erences during etomidate anesthesia, but this needs further study [18].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic contribution to the effi cacy and safety profi le of etomidate is still poorly understood. One study showed that GABRA2 rs279858, GABRB2 rs2561, CYP2C9 rs1559 and UGT1A9 rs11692021 variants were associated with individual diff erences during etomidate anesthesia, but this needs further study [18].…”
Section: Intravenous Anestheticsmentioning
confidence: 99%
“…Propofol activates GABA receptors, blocks NMDA glutamate receptors and prevents calcium from entering the cell [18]. One recent study analyzed genes possibly related to the pharmacological profile of propofol.…”
Section: Intravenous Anestheticsmentioning
confidence: 99%